Compression ellipsoidal cavities - Буйвол, В.М. (Proceedings of National Aviation University, 2007)
The process of ellipsoidal cavity (bubble) compression in liquid is considering. The mathematical model and its computational realization are proposed. The dependences of basic cavity dimensions on ellipsoid parameters, flow regime and time are investigating.